A QUESTÃO SOCIAL NO CAPITALISMO CONTEMPORÂNEO: COMO O ESTADO ENFRENTA A QUESTÃO SOCIAL? - dos Santos Brito, Flavio (Revista Serviço Social em Perspectiva, 2021)
The social question constitutes the essence of the practical and theoretical process of social work intervention. It is inscribed in the most diverse segments of professional activity and is thus intertwined as an object of theorization for better understanding and elucidation. The social issue is thus closely linked to the historical process of commodification of the economy and finds in the state apparatus a strongly promoting agent of social, economic, democratic and political disparities in civil society in its most varied class compositions.